Os motivos da relação entre orientação para o empreendedorismo e desempenho organizacional - Reis, Fábio Krieger Lopes (2015)
The strategic orientation has been widely studied to understand how organizations can increase their organizational performance. Therefore, it is believed that through appropriate strategies organizations may compete efficiently and effectively. In this regard, entrepreneurial orientation has been widely associated to superior performance. Based on these considerations, this study aims to understand the reasons for the positive impact of entrepreneurial orientation in relation to organizational performance. Therefore, a literature survey was conducted to understand the reasons that relate this approach with improved performance. After, a qualitative survey was conducted to recognize the reasons for this relationship in the perception of market experts. The results reinforced the notion that entrepreneurial orientation positively impacts organizational performance and that several reasons support this relationship. Thus, the reasons found were grouped into four categories: people management, organizational skills, marketing skills and adaptability. This set of reasons was associated with organizational higher performance. It is understood, through the opinion of experts, especially a relevancy of the people who are affected by the entrepreneurial orientation and driving the other corporate virtues in favor of the organizational performance.